2023
DOI: 10.1101/2023.01.25.525562
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ageing impairs the regenerative capacity of regulatory T cells in central nervous system remyelination

Abstract: Myelin regeneration (remyelination) is essential to prevent neurodegeneration in demyelinating diseases such as Multiple Sclerosis but its efficiency declines with age. Regulatory T cells (Treg) recently emerged as critical players in tissue regeneration, including remyelination. However, the effect of ageing on Treg-mediated regenerative processes is poorly understood. Here, we show that expansion of aged Treg does not rescue age-associated remyelination impairment due to an intrinsically diminished capacity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 69 publications
(129 reference statements)
0
1
0
Order By: Relevance
“…Age-related alterations in DNA methylation patterning are a core hallmark of aging (108), and in our study, genome-wide DNA methylation profiling revealed that age-related epigenetic alterations explained the loss of reparative transcriptional programs following influenza infection. Beyond the lung, a growing body of literature suggests that age-related Treg dysfunction affects other tissues and organs, including adipose tissue, skeletal muscle, and the nervous system (29,111,112). In addition to age, sex and gender are important biological and demographic variables, respectively, that are associated with differential risks from severe pneumonia, including due to SARS-CoV-2, with male sex and gender consistently demonstrating increased susceptibility (113)(114)(115).…”
Section: R E V I E W S E R I E S : L U N G I N F L a M M At O Ry I N ...mentioning
confidence: 99%
“…Age-related alterations in DNA methylation patterning are a core hallmark of aging (108), and in our study, genome-wide DNA methylation profiling revealed that age-related epigenetic alterations explained the loss of reparative transcriptional programs following influenza infection. Beyond the lung, a growing body of literature suggests that age-related Treg dysfunction affects other tissues and organs, including adipose tissue, skeletal muscle, and the nervous system (29,111,112). In addition to age, sex and gender are important biological and demographic variables, respectively, that are associated with differential risks from severe pneumonia, including due to SARS-CoV-2, with male sex and gender consistently demonstrating increased susceptibility (113)(114)(115).…”
Section: R E V I E W S E R I E S : L U N G I N F L a M M At O Ry I N ...mentioning
confidence: 99%